Невеста с сюрпризом: роман / Сандра Браун - Браун Сандра (Эксмо, 2002)
Экземпляры: ф.11 (2003) / Инвентарный номер: 47512 / Цена: / Сис.шифр: 84(7Сое)-44 / Авт.знак: Б 87 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44